The Importance of Supervision of Parents Against Sexual Harming Threats in Early Childhood in Digital Era - Ismaniar Ismaniar (Universitas Negeri Padang, 2020)
The rise of the phenomenon of sexual abuse in early childhood amid the rapid development of information technology is something that needs to be addressed seriously. Adverse effects that occur due to sexual abuse in early childhood are not only felt by the victim in a short period of time but will also be felt and affect the development of the psychological and mental aspects of the child after he is an adult. Parents as the main responsible for children's healthy growth and development must be able to ensure that their children avoid the threat of crime, one of which is the threat of sexual abuse. Good supervision is the key to the success of parents in keeping their children from becoming victims of sexual harassment. Therefore, parents must master a variety of strategies or ways to teach and get used so that children can avoid the targets of sexual abuse predators. Among the strategies that parents can do are, establish intense communication with children, teach them to be brave to say no and reject persuasions or enticements of others, discipline in saying, behaving and acting, independent according to their age and teaching about body parts that are personal to him and should not be seen, touched and held by others.Keywords: Supervision, Threats, Sexual Harassment, Early Childhood, Digital Era